Interest Comparison on Paylater Schemes: Case Study on E-Commerce Shopee and Tokopedia - Mahdy, Aid Daffa; Rusmana, Dadan (International Journal of Global Operations Research, 2025)
In recent years, paylater services in e-commerce, such as Shopee and Tokopedia, have experienced rapid growth by offering consumers the convenience of flexible shopping without paying in advance. This study aims to analyze the comparison of simple and compound interest models applied in the paylater schemes of the two platforms, with a focus on their impact on total payments and users' financial decisions. Primary data is obtained from the fee structure and interest rates applied by Shopee and Tokopedia, while secondary data is taken from related literature. The study used a quantitative approach with a case study method, involving payment simulations based on various nominal transaction scenarios (IDR 500,000, IDR 1,000,000, IDR 5,000,000) and tenors (3, 6, 12 months) calculated using Microsoft Excel. The results of the study show that Tokopedia offers a more economical fee structure, especially for large amounts and long tenors, with an interest of 2.75% per month and a fixed handling fee of IDR 5,000. In contrast, Shopee, although applying an interest of 2.95% per month, has a higher total payment due to a percentage-based handling fee of 1%. This study provides recommendations to users to choose a platform according to their financial needs. Tokopedia is recommended for large transactions and long tenors, while Shopee is more suitable for small transactions with short tenors. These results are also expected to be a reference for service providers to adjust their policies to improve competitiveness and user satisfaction. This study provides in-depth insight into the influence of interest models in paylater schemes and helps users make wiser financial decisions.